To the question of academic discipline "Fundamentals of medical knowledge and children's health protection" - Glazkova I.B (Kharkov National Pedagogical University, 2012)
The paper provides theoretical grounds for the supplementation to the contents of the curriculum on the fundamentals of medical knowledge for the students of higher educational pedagogic institutions. It gives the conceptual framework for Primary Prevention of Noncommunicable Diseases module presented in the discipline of Fundamentals of Medical Knowledge and Children's Health Protection. It stresses the necessity of educating future teachers on the importance of primary and secondary noncommunicable diseases prevention work.